EFFICACY OF ANTIHYPERTENSIVE THERAPY WITH ADDED ANTIDEPRESSANT IN HYPERTENSION PATIENTS AND DEPRESSION - D. V. Kovalev; V. V. Skibitskiy; A. N. Kurzanov; A. I. Ponomareva (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To compare the influence of monoand combined with antidepressant antihypertension therapy (AHT) on the parameters of 24-hour blood pressure (BP) profile, severity of depression and life quality of patients with non-controlled arterial hypertension (AH) and depression.Material and methods. 71 patients, aged 48,7±5,2 y.o., 37 females, were randomized to two groups. Each group during a year consequently received two types of pharmacotherapy for 6 months twice: mono AHT and AHT with antidepressant fluvoxamine (AHT+A). Group 1 (n=35) for the first half-year received AHT, then AHT+A; group 2 (n=36) in reversed order. At the end of each half-year, we compared 24-hour blood pressure, and severity of depression by Beck score, with life quality. Same comparisons were done in the group by endings of two periods.Results. Starting with combination AHT led to faster achievement of relatively low values of mean day and mean night systolic and diastolic BP, lower BP variability. Combination AHT made to reach significantly higher level of the value and velocity of morning BP raise. Only combination therapy showed adequate reduction of depression symptomathics. Combination, as monotherapy in 6 month led to significant improvement of life quality; however, combination therapy was significantly better.Conclusion. Efficacy of antidepressant-combined AHT with fluvoxamine in AH patients with depression better than mono AHT.